Analisis Kepercayaan Pelanggan E-Commerce Berdasarkan Persepsi Pembeli - Emha Diambang Ramadhany; Muhammad Qomarul Huda; I Dewa Made Yuda Mahendra (Jurnal Simki Economic, 2023)
E-commerce is a medium of online trading that will help the efficiency and productivity of buying and selling for business owners and consumers. Less physical presences both parties raised doubts on consumers to transact online. Therefore, trust is a key factor in transactions. Therefore, the trust in e-commerce needs to be addressed. An analysis is done by examine what factors can improve the Indonesian's trust in e-commerce. The research model is adapted from the selected previous research models which consisted of six hypotheses The study sampling method was purposive sampling technique. 102 main samples is obtained to be analyzed. Hypothesis test results stated that the website quality / application has a significant effect on customer trust. This means that factor that makes increase trust for online transactions is a good quality website of an online store. The quality of a good website including quality of information, ease of use, the actuality of the product, and the service quality on the website.